Performance of Graphene Nanopowder-Polyvinyl Alcohol in Optical Pulse Generation at 1.5 Micron Region - Hussain, Nabihah; Salim, Mohd Rashidi; Azmi, Asrul Izam; Mohd Noor, Muhammad Yusof; Abdullah, Ahmad Sharmi; Ahmad, Fauzan; Mohd Haniff, Ibrahim (Photonics Letters of Poland, 2021)
This paper explains about the performance of graphene nanopowder (GNP) based saturable absorber (SA) at 1.5-micron region which is prepared by dissolution in polyvinyl alcohol (PVA) polymer. Two different GNP flakes thickness (AO2-8 nm and AO4-60 nm) are tested. By applying a solution casting method, three weight ratio of GNP to PVA (12.04, 8.03 and 3.11 wt.%) have been prepared and fabricated as a composite thin film. To characterize for the SA performance, 4 mm2 area of GNP-PVA thin film is embedded in a 14 meters long ring cavity with 3 meters Erbium doped fiber (EDF) as a gain medium. Our characterization results show that the GNP-PVA thin film act as a Q-switcher which produce stable laser pulses for 12.04 wt.% with maximum repetition rate of 39.22 kHz and shortest pulse width of 11.79 µs. Meanwhile, unstable Q-switched pulses of 8.03 wt.% and 3.11 wt.% have been observed with recorded signal to noise ratio (SNR) of only 21 dB and 17 dB, respectively. The threshold pumping power for Q-switched lasing to emerge is recorded as low as 30 mW. Apparently, it shows that GNP concentration and flakes thickness in fabricated SA composite plays vital role in the performance of generated Q-switch laser, particularly at 1.5 µm region. Full Text: PDF References T. Hasan, Z. Sun, F. Wang, F. Bonaccorso, P.H. Tan, A.G. Rozhin, A.C. Ferrari, "Nanotube–Polymer Composites for Ultrafast Photonics", Adv. Mater. 21, 3874 (2009). CrossRef Q. Bao, H. Zhang, Y. Wang, Z. Ni, Y. Yan, Z.X. Shen, K.P. Loh, D.Y. Tang, "Atomic-Layer Graphene as a Saturable Absorber for Ultrafast Pulsed Lasers", Adv. Funct. Mater. 19, 3077 (2009). CrossRef Z. Luo, M. Zhou, J. Weng, G. Huang, H. Xu, C. Ye, Z. Cai, Opt. Lett. 35(21), 3709 (2010). CrossRef D. Popa, Z. Sun, T. Hasan, F. Torrisi, F. Wang, A.C. Ferrari, "Graphene Q-switched, tunable fiber laser", Appl. Phys. Lett. 98, 3106 (2011). CrossRef Y.M. Chang, H. Kim, J.H. Lee, Y. Song, "Multilayered graphene efficiently formed by mechanical exfoliation for nonlinear saturable absorbers in fiber mode-locked lasers", Appl. Phys. Lett. 97, 211102 (2010). CrossRef M. Jiang, Z. Ren, Y. Zhang, B. Lu, R. Zhang, J. Guo, Y. Zhou, J. Bai, "Passive Q-Switching with Graphene Saturable Absorber in Nd:YAG Operating at 1064nm", Mater. Sci. Forum 694, 700 (2011). CrossRef N. Hussin, M.H. Ibrahim, F. Ahmad, H. Yahaya, S.W. Harun, "Graphene Nanoplatelets (GnP)-PVA Based Passive Saturable Absorber", Telkomnika 15(2), 814 (2017). CrossRef F.C. Mat, M. Yasin, A.A. Latiff, S.W. Harun, Photonics Letters of Poland 9, 100 (2017). CrossRef E.K. Ng, K.Y. Lau, H.K. Lee, N.M. Yusoff, A.R. Sarmani, M.F. Omar, M.A. Mahdi, "L-band femtosecond fiber laser based on a reduced graphene oxide polymer composite saturable absorber", Opt. Mater. Express 11, 59 (2021). CrossRef N.H.M. Apandi, S.N.F. Zuikafly, N. Kasim, M.A. Mohamed, S.W. Harun, F. Ahmad, "Observation of dark and bright pulses in q-switched erbium doped fiber laser using graphene nano-platelets as saturable absorber", Bull. Electr. Eng. Inform. 8, 1358 (2019). CrossRef N.U.H.H.B. Zalkepali, N.A. Awang, Y.R. Yuzaile, Z. Zakaria, A.A. Latif and F. Ahmad, "Graphene Nanoplatelets as Saturable Absorber for Mode-locked Fiber Laser Generation", J. Adv. Res. Dyn. Control Syst. 12(2), 602 (2020). CrossRef X. Zhu and S. Chen, "Autoencoder-Based Transceiver Design for OWC Systems in Log-Normal Fading Channel", IEEE Photonics J. 11, 7105109 (2019). CrossRef